Guardare il Tanztheater: una riflessione sulla fruizione del teatro di Pina Bausch (Mantichora. Italian Journal of Performance Studies, 2020)
This contribution aims at analysing Pina Bausch’s theatrical activity as an example of some tendencies in contemporary performing art – with a special eye on the domains of emotionality and empathy. The analysis starts off some formal aspects of Tanztheater which are characterised by a strong compositional synergy and result in an interconnection of corporal, visual and sonic elements that create peculiar and complex tempos and play structures. Emotionality is the true core of Pina Bausch’s creative work: using the figurative power of the images represented, Pina Bausch does not just show: she evokes, suggests and refers to. The performance involves the audience in a multisensory and synaesthetic way; the staging is where the artist’s creation meets the viewer’s sensitivity meets the public’s response.